PERANCANGAN SISTEM PENGGAJIAN EFISIEN BERBASIS UML PADA PERUSAHAAN SKALA KECIL - Arum Tri Iswari Purwanti; Albertus Bayu Aji Priyono (Asosiasi Dosen Muda Indonesia, 2025)
An efficient and accurate payroll system is essential for small businesses to ensure employee satisfaction while maintaining smooth operational processes. This study aims to design and develop a payroll system based on Unified Modeling Language (UML), specifically tailored for small businesses with 50–100 employees. The system includes processes such as employee data collection, salary calculation, validation, approval, payment, and reporting. UML design is utilized to model the system workflow, including use case diagrams, activity diagrams, and class diagrams. The implementation results demonstrate that the system can reduce calculation errors by up to 90% and improve data processing time by 50%. Additionally, the system provides transparent reporting features to support financial decision-making. With its development flexibility, the system can be adapted for further integration, such as attendance modules or tax reporting. This study makes a significant contribution to enhancing the efficiency and professionalism of payroll management in small businesses.